2020
DOI: 10.3390/molecules25010233
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical Characterization, Genetic Profile, and Antiproliferative Activity of Polyphenol-Rich Extracts from Pigmented Tubers of Different Solanum tuberosum Varieties

Abstract: Plants produce a vast array of biomolecules with beneficial effects for human health. In this study, polyphenol and anthocyanin-rich extracts (PAE) from pigmented tubers of Solanum tuberosum L. varieties “Blue Star”, “Magenta Love”, and “Double Fun” in comparison with the more extensively studied “Vitelotte” were evaluated and compared for antiproliferative effects in human leukemia cells, and their phytochemical and genetic profiles were determined. In U937 cells, upon treatment with PAE, it was possible to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Some biological effects have been described for the polyphenolic extracts of colored potatoes and give them beneficial effects towards some cancers [ 17 ], as anticarcinogenic effects of anthocyanin extracts, which serve as suppressors of early and advanced cell proliferation and inductors of apoptosis in colon cancer under in vitro and in vivo conditions [ 18 ], and also in human leukemia cells [ 19 ]. The anthocyanins from purple-fleshed potatoes have also been reported that decreases postprandial glycemic response and affect inflammation markers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some biological effects have been described for the polyphenolic extracts of colored potatoes and give them beneficial effects towards some cancers [ 17 ], as anticarcinogenic effects of anthocyanin extracts, which serve as suppressors of early and advanced cell proliferation and inductors of apoptosis in colon cancer under in vitro and in vivo conditions [ 18 ], and also in human leukemia cells [ 19 ]. The anthocyanins from purple-fleshed potatoes have also been reported that decreases postprandial glycemic response and affect inflammation markers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these evidences support the suitability of these feedstock to be valorized as new products in a circular economy viewpoint. S. tuberosum peelings have previously investigated as potential source of new crude glycoalkaloid [ 58 ], polyphenolic [ 59 ], and polyphenolic/anthocyanin [ 60 ] antimicrobials. In addition, these natural compounds are characterized by a low persistence in the environment (the half-live of α-solanine has been estimated to vary in the range 1.8–4.1 days at 15 °C), features that makes them suitable for the field application in a perspective of ecofriendly control of plant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin publications in PubMed have gone from under 200 per year in 2000, to over 1000 in 2018, in part due to interest in their health-promoting effects [ 234 ]. Purple-flesh potatoes with high amounts of polyphenols and anthocyanins have shown benefits in several health studies, including induction of apoptosis, anti-cancer and anti-diabetes properties and promotion of gut health [ 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 ]. Anthocyanins from purple potatoes reduced alcohol-induced hepatic injury in mice [ 254 ].…”
Section: Phenolic Antioxidantsmentioning
confidence: 99%